Clinical guidelines for burosumab in the treatment of XLH in children and adolescents: British paediatric and adolescent bone group recommendations. Issue 10 (October 2020) - Padidela, Raja; Cheung, Moira S; Saraff, Vrinda; Dharmaraj, Poonam
Abstract : X-linked hypophosphataemia (XLH) is caused by a pathogenic variant in the PHEX gene, which leads to elevated circulating FGF23. High FGF23 causes hypophosphataemia, reduced active vitamin D concentration and clinically manifests as rickets in children and osteomalacia in children and adults. Conventional therapy for XLH includes oral phosphate and active vitamin D analogues but does not specifically treat the underlying pathophysiology of elevated FGF23-induced hypophosphataemia. In addition, adherence to conventional therapy is limited by frequent daily dosing and side effects such as gastrointestinal symptoms, secondary hyperparathyroidism and nephrocalcinosis. Burosumab, a recombinant human IgG1 MAB that binds to and inhibits the activity of FGF23, is administered subcutaneously every 2 weeks. In clinical trials (phase 2 and 3) burosumab was shown to improve phosphate homeostasis that consequently resolves the skeletal/non-skeletal manifestations of XLH. Burosumab was licensed in Europe (February 2018) with the National Institute for Health and Care Excellence, UK approving use within its marketing authorisation in October 2018. In this publication, the British Paediatric and Adolescent Bone Group (BPABG) reviewed current evidence and provide expert recommendations for care pathway and management of XLH with burosumab.